Behavior of 1-octanol and biphasic 1-octanol/water droplets in a digital microfluidic system - Jan Wagner; Oliver Fiukowski; Roman Nebesnyi; Sven Ingebrandt; Andrij Pich; Uwe Schnakenberg (Micro and Nano Systems Letters)
Abstract Digital microfluidic systems, based on the electrowetting-on-dielectric mechanism, allow the manipulation, dispensing, merging, splitting, and mixing of micro- to nanoliter droplets on hydrophobic surfaces by applying voltages to an array of planar electrodes. The manipulation of both a non-aqueous and an aqueous phase droplet in a single experiment has gained considerable interest. This study focuses on characterizing the dispensing and dosing of 1-octanol droplets, merging with a water droplet, and phase separation with minimal residue formation by shearing off the biphasic droplet at a tear-off edge of a hydrophilic well, using optimized actuation parameters. The volume of the 1-octanol droplet dispensed from an L-junction reservoir design increased with increasing dispensing speed. Dispensing can only occur within a certain reservoir volume range. Under identical conditions, 1-octanol droplets could be dispensed with volume variations of less than 0.55%, and manipulated at a maximum velocity of 5.6 mm/s when the frequency of the applied AC voltage was about 200 Hz. At the tear-off edge of the hydrophilic well, the 1-octanol residue on the water droplet was reduced to less than 0.15% of the original 1-octanol droplet volume. The results will be used for future applications, such as for the precise quantitative characterization of the reaction kinetics of complex parallel or sequential interfacial catalytic reactions, for the study of self-assembly processes or for liquid–liquid extractions at the 1-octanol–water interface.